ChemInform Abstract: An Efficient One‐Pot Synthesis of Aryl‐Substituted 1‐(Thiazol‐2‐yl)‐1H‐pyrazole‐3‐carboxylates via a Hantzsch Synthesis‐Knorr Reaction Sequence. Issue 29 (22nd July 2014) - Gu, Chunhui; Zhai, Jiaojiao; Jiang, Jianan; Liu, Hongwei; Wang, Lei; Zhu, Dunru; Ji, Yafei
Abstract A great variety of title compounds is conveniently synthesized by reaction of thiazoles obtained by Hantzsch synthesis with previously prepared enolic lithium salts of diketoesters.